Recursos didáticos e inclusivos para o ensino do meio ambiente - MORAES, Kauê Felippe de (Universidade Federal do Pará, 2021)
This article refers to the use of didactic and inclusive resources for the teaching of Environment, experience carried out in a class of PARFOR students who work in Primary Education with the discipline Biology. It aims to analyze the difficulties faced by these teachers who work with visually impaired students (blind/low vision). The methodology, based on qualitative research, took place in three different stages and culminated in the workshop entitled "Didactic and Inclusive Resources for Teaching the Environment", where the use of an "Inclusive Domino over the Environment" was built and experimented. The results show that the academics present experiences in the education of visually impaired students. However, there are still difficulties in promoting inclusive education in regular education.